ANALISIS BIAYA PENYULINGAN MINYAK GAHARU BUDIDAYA DI TENGGARONG, KALIMANTAN TIMUR - Tien Wahyuni; Helsa Yuliana (Jurnal Penelitian Hasil Hutan, 2021)
One possible way to improve the value added of low quality agarwood (medang, sapuan, sabak) is by refining it to produce oil.Gaharu oil is used as raw material for several products such as raw material for perfumes, cosmetics and traditional medicines.This agarwood refining research aims to determine the oil yield, by products, to analyze the maximum cost, income and profit duringone refining period in the household-scale refining industry. This research was conducted in the household scale agarwood oil refiningindustry located in Rempanga Village, Loa Kulu Tenggarong Subdistrict, Kutai Kartanegara Regency. The results of this studyare expected to provide motivation to various parties to be able to utilize the quality of low-quality cultivated agarwood efficientlyand optimally through product diversification by refining it to produce high-value agarwood oil. The observation procedure is carriedout directly during the distillation process. Economic value is obtained by analyzing break even point (BEP) and maximum income.The results showed that the yield of agarwood oil was 0.07%. At the level of agarwood oil production of 30 mililiter (ml) per oneproduction period with a selling price of Rp 250,000/ml will break even if the agarwood oil produced is 1.93 ml with a value ofRp 482,159.88 or Rp 16,071.99/unit (ml). The business profit at the production level of 30 ml of agarwood oil is Rp 3,616,830(without sales of powdered waste and agarwood hydrosol) and Rp 8,316,830 (with sales of powdered waste and agarwood hydrosol).